High-power laser-driven phosphor-in-glass for excellently high conversion efficiency white light generation for special illumination or display backlighting. Issue 30 (23rd July 2018) - Yu, Jinbo; Si, Shuaichen; Liu, Yong; Zhang, Xuejie; Cho, Yujin; Tian, Zifeng; Xie, Rongjun; Zhang, Hongwu; Li, Yurong; Wang, Jing
Abstract : High-power and high-brightness solid state laser lighting sources, fabricated with high-power blue laser diodes (LDs) and yellow-emitting phosphor converters, constitute a pioneering lighting technology for specialized lighting. Abstract : High-power and high-brightness solid state laser lighting sources, fabricated with high-power blue laser diodes (LDs) and yellow-emitting phosphor converters, constitute a pioneering lighting technology for specialized lighting. Because of the high radiation flux and thermal stress produced by high-power blue LDs, there is an urgent need for a light converter with excellent heat-resistance and thermal stability. In this work, YAG:Ce phosphor-in-glass (PiG), prepared by embedding YAG:Ce phosphor in glass matrix, was developed. Because of the good chemical stability between the glass matrix and the phosphor as well as high refractive index of 1.84 of the glass matrix, the internal quantum efficiency of YAG:Ce-PiG material can reach up to 78.9% under 445 nm blue laser excitation. In comparison with reported papers, the content of the YAG phosphor in this PiG can reach up to 29 wt%, thus it can get more brightness when excited by higher LD power. Besides, systematic research on the thermal effect to the material and its luminescent properties when excited by a high-power blue LD is done in detail. Compared with traditional commercial phosphor-in-silicone (PiS) light converters, PiG can withstand higher blue LD power and maintain a higher luminescent intensity. By virtue of its better heat-resistance performance under exposure to high-power blue LD, the developed PiG light converter material is an ideal choice to replace traditional commercial PiS in high brightness lighting sources.